Masquerade : a novel - Dailey, Janet (Little, Brown, 1990)
Remy Jardin, suffering from amnesia after an attack in Nice, risks losing the man she loves, Cole Buchanan, as well as her own life, as she searches for the truth about an accident involving her family's shipping company.